Blast protection of concrete columns with thin strips of GFRP overlay. (June 2020) - Vapper, Meelis; Lasn, Kaspar
Abstract: Reinforced concrete columns are basic structural elements found in many buildings. Studies of their structural behaviour are typically concerned with quasi-static loading conditions. Lately, an interest into loading effects from explosive blasts has emerged. This is due to unconventional hazards such as global terrorism. Implementing a standoff distance between a building and a potential hazard is not always possible, especially in urban environments. Other strategies of blast protection must be considered. Current experimental work was carried out to test the effectiveness of structural strengthening of concrete columns by thin strips of glass fibre reinforced polymer overlay. The specific reinforcement arrangement was chosen for its low cost and for ease of application. Concrete columns were designed and produced in model-scale proportions. Matching pairs of regular and retrofitted columns were loaded by short clearance detonations. Regular rebar reinforced columns and short steel fibre reinforced columns were tested. Retrofitting improved the residual compressive strength of short fibre reinforced columns. The overall fragmentation/spalling effects for concrete were also reduced. The strength improvements for rebar reinforced columns were insignificant, due to specifics of the retrofit scheme.